Plant interactions with arthropods and pathogens at Sanzenbacher Ranch, early Permian of Texas, and implications for herbivory evolution in Southwestern Euramerica - Dos Santos, Thamiris Barbosa; Labandeira, Conrad C.; Pinheiro, Esther Regina de Souza; Iannuzzi, Roberto (Frontiers in Ecology and Evolution, 2024)
The Sanzenbacher Ranch deposit represents an early Permian plant assemblage in north-central Texas predominantly composed of pteridosperms, of which callipterids are dominant. This study investigates the interactions of a taxonomically broad range of plant hosts with insects, mites, and pathogens to assess the richness and frequency of damage. Of total surface area represented, we quantified the fraction of the area herbivorized, providing a comparative perspective with regard to several similar studies of herbivory at nearby plant assemblages from the late Paleozoic. To assess insect herbivory, 1361 plant specimens were analyzed, including fronds, leaves, reproductive structures, axes, and wood impressions. A total of 205 specimens presented one or more instances of insect herbivory (11.17%). Callipterid-peltasperms exhibited the highest number of interactions, with Autunia conferta, Rhachiphyllum schenkii, cf. Lodevia sp., cf. Comia sp., and an unidentified callipterid accounting for 49.34% of all interactions. Medullosans represented 10.53%, followed by lyginopterids with 8.55%. Forty-eight damage types (DTs) were recognized and classified into the nine functional feeding groups of hole feeding, margin feeding, surface feeding, piercing and sucking, oviposition, galling, seed predation, borings, and pathogens. When compared to analogous late Paleozoic plant assemblages in Texas, Sanzenbacher Ranch exhibited almost all herbivore functional feeding groups, high richness of DTs, and low herbivory index of 0.26. This record shows high plant diversity in a seasonally dry environment that supports a trend of an early Permian increase in DT diversity in southwestern Euramerica. Sanzenbacher Ranch, different from other early Permian plant assemblages, sheds light on the dynamic ecological interactions of these ancient ecosystems.